Fusiform Activity Distinguishes Between Subjects With Low and High Xenophobic Attitudes Toward Refugees - Kesner, Ladislav; Fajnerová, Iveta; Adámek, Petr; Buchtík, Martin; Grygarová, Dominika; Hlinka, Jaroslav; Kozelka, Pavel; Nekovářová, Tereza; Španiel, Filip; Tintěra, Jaroslav; Alexová, Aneta; Greguš, David; et al. (Frontiers in Behavioral Neuroscience, 2020)
This study analyzes how people's attitudes to the European refugee crisis (ERC) correspond to selected psychological state and trait measures and impact the neural processing of media images of refugees. From a large pool of respondents, who filled in an online xenophobia questionnaire, we selected two groups (total N = 38) with the same socio-demographic background, but with opposite attitudes toward refugees. We found that a negative attitude toward refugees (high xenophobia - HX) was associated with a significantly higher conscientiousness score and with a higher trait aggression and hostility, but there was no group effect connected with empathy, fear, and anxiety measures. At the neural level we found that brain activity during the presentation of ERC stimuli is affected by xenophobic attitudes—with more xenophobic subjects exhibiting a higher BOLD response in the left fusiform gyrus. However, while the fMRI results demonstrate increased attention and vigilance toward ERC-related stimuli in the HX group, they do not show differentiated patterns of brain activity associated with perception of dehumanized outgroup.